Między rzeczywistością a ideałem— o profilowaniu obrazu demokracji w polskim i niemieckim dyskursie feministycznym - Grzeszczak, Monika (Stylistyka, 2021)
The goal of the article is to analyze the image of democracy in Polish and German feminism discourse, the way democracy is conceptualized and differentiated. The Author uses the defmite notions applied in ethnolinguistic analyses conducted by the Lublin Eth- nolinguistic School, such as: profiling the notions, projile, thepoint of view, interpretation perspective. The analysis of the collected data leads to the dififerentiation of two basie profiles of democracy: to the real one (oriented towards description) and to the ideał one (expressed with postulates), where the real profile dominates in the discourse of Polish feminism and the ideał profile - in the discourse of German feminism. In the framework of the chief profiles, the Author points out the political profiles in the following discourses: the profile of world-view in Polish discourse, and the social one - in German discourse. The given analysis shows different points of view: the Polish feminists talk about domi- nating and the redundant role of men (in politics particularly), whereas the German feminists talk about the of women in political, social and professional spheres. The presented differences occur as the result of the accepted values. In Polish discourse democracy is used in collocations with the following notions - values: równoace (equality (of rights)), wolnoceoe (freedom, independence), normalnooece (normalization, standarization), whereas in German discourse we meet Gerechtigkeit (justice, equity, faimess), Frieden (pe- ace), Gewaltfreiheit (the absence of violence, coercion, constraint), Wohlstand (welfare, wellbeing, prosperity).